National Fertility Survey, 1970 - Westoff, Charles F. ([Verlag nicht ermittelbar], 2008)
The 1970 National Fertility Survey (NFS) was the second in a series of three surveys that followed the Growth of American Families surveys (1955 and 1960) aimed at examining marital fertility and family planning in the United States. Women were queried on the following main topics: residence history, age and race, family background, pregnancies, abortions and miscarriages, marriage history, education, employment and income, religion, use of family planning clinics, current and past birth control pill use and other methods of contraception, sterility, ideals regarding childbearing, attitudes and opinions with respect to abortion, gender roles, sterilization and world population, and birth histories. Respondents were asked to give residence histories for themselves and their husbands. Specifically, they were asked about the state they grew up in, whether they had lived with both parents, whether they had lived on a farm growing up, and whether they were currently living on a farm. Respondents were asked to give their date of birth, current age and race, as well as that of their husband. Regarding family background, respondents were asked how many brothers and sisters that they had, whether their siblings were older or younger, and whether there were any twins in the family. Additionally, respondents were asked to summarize their pregnancy history by giving information with respect to total number of pregnancies, live births, miscarriages, and abortions. Regarding abortions, respondents also were asked to give the date of the abortion and if they had used any family planning techniques prior to the abortion. Respondents were queried about their marriage history, specifically they were asked whether this was their first marriage, whether it was their spouse's first marriage, and their total number of marriages. If previously married, respondents were asked about the dates of past marriages and reasons for the marriage ending (e.g., death, divorce, or annulment). Respondents were asked a series of questions about both their own and their spouse's education including number of grades completed, current educational status, schooling completed after marriage, highest grade completed, and highest grade the respondent and spouse hoped to complete. All respondents were queried about their own and their husband's employment situations, as well as their household income. Respondents were asked about employment prior to and after marriage, employment after the birth of their first child, reasons for working, future employment expectations, earned income for both the respondent and husband in 1970, and other sources of income. There was also a series of questions on religion including religious preferences growing up, current religious preferences, and the importance of religion for both the respondent and her husband. Respondents were asked whether they had ever been to a family planning clinic, whether methods of family planning were discussed with a doctor or other medically trained person, whether this had taken place in the last 12 months, and if not, when the last time was. Several questions were devoted to the respondent's current and past use of the birth control pill and other methods of contraception such as the IUD and the diaphragm. Specifically, respondents were asked how they obtained the method of contraception for the first time, whether the respondent had sought methods of contraception from a doctor, and whether they had discussed with a doctor problems related to the methods of contraception. Respondents were asked why they used the pill and other methods of contraception, why they had stopped using a particular method, whether the methods were being used for family planning, and during what intervals the methods were used. Respondents also were asked questions about sterility including whether they were able to have children, whether they or their husband had undergone a sterilization operation, and if so, what kind of operation it was, the motive for having such an operation, whether the respondent had arrived at menopause, and if they had seen a doctor if they were unable to have a baby. They were also asked about their ideals with respect to children including their ideal number of children, the ideal number of boys and girls, as well as the ideal age for having their first and last child. The survey also sought each respondent's opinions regarding abortion, such as when, if ever, it was acceptable, the legal status of abortion, gender roles at home and in the work place, and world population and the gravity of the problem relative to other problems such as poverty, race relations, and nuclear war. Respondents were also asked to give detailed birth histories describing all live births, total number of wanted and unwanted children, total number of wanted and unwanted pregnancies, planning status by birth order, and the date and order of the last wanted birth.